IMPLEMENTATION OF FUZZY TOPSIS METHOD FOR ADMISSION SELECTION SYSTEM IN ACCELERATION CLASS - Mutmainah, Nina; -, Yulmaini (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Acceleration class is the class known as Kelas Siswa Cerdas Istimewa (SCI). This class facilitates special students who take the Senior High School for 2 years. The selection of the Acceleration Class at State Senior High School 9 Bandar Lampung uses the average score through Microsoft Excel. The problem statement of this research was that the final result of this selection was printed, announced on the announcement board, or announced directly to students who passed the test so that the selection process was inefficient and unobjective. This problem raised the idea to make the systems for the selection process of this Acceleration Class. The method used in this research was the Fuzzy TOPSIS with the certain criteria i.e., the average score of UN, the average report card, the IQ test, the specialization test, the achievement, and the financial condition. The result of this research showed that 8 of 20 students successfully passed to the acceleration class by the consideration that the students who reached the passing grade was > = 0.7 and the students who did not reach the passing grade was < 0.7. Therefore, this research was also successfully generated the website-based system for the admission selection systems in the Acceleration Class.Keywords: Fuzzy TOPSIS, selection, acceptance, acceleration class